The stem-archosaur evolutionary radiation in South America - Ezcurra, Martín D.; Montefeltro, Felipe C. [UNESP]; Pinheiro, Felipe L.; Trotteyn, M. Jimena; Gentil, Adriel R.; Lehmann, Oscar E.R.; Pradelli, Luciano A. (Elsevier, 2021)
The oldest archosauromorphs (dinosaurs, birds, crocodiles, and their stem-taxa) are recorded in middle−upper Permian rocks, but it was not after the Permo−Triassic mass extinction that the group shows a substantially high taxonomic richness and ecomorphological disparity. The early evolutionary history of the Archosauromorpha during the Early and Middle Triassic is mainly based on fossils recovered from rocks in southern Africa, Europe and Asia, whereas South America possesses a more complete fossil record of the group only in the Late Triassic. Here we revisit, discuss, and reanalyse the non-archosaurian archosauromorph fossil record of the current-day South America. The Early Triassic archosauromorph record in this continent is still scarce, but it documents the early evolution of the group in western Pangaea and is crucial to understand more globally the biotic recovery after the Permo−Triassic mass extinction. The Middle Triassic record is extremely scarce, but the Late Triassic archosauromorph assemblage of South America is among the most diverse and abundant worldwide. The last decade has witnessed a considerable improvement in our knowledge of the record, taxonomy, phylogeny, and macroevolution of the group with the input from the South American fossils. Nevertheless, a considerable amount of research is needed and ideally should be focused on some particular aspects of the Triassic evolutionary radiation of Archosauromorpha. Among them, the Early Triassic record should be expanded, more numerous and more complete Middle Triassic archosauromorph specimens are crucial to have a more complete picture of the evolution of the group, and the taxonomy of groups like proterochampsids and hyperodapedontine rhynchosaurs should be clarified through detailed anatomical work.
Keywords: Anatomy; Archosauromorpha; Argentina; Brazil; Macroevolution; Phylogeny; Proterochampsidae; Proterosuchidae; Rhynchosauria; Uruguay